The burden of premature mortality of epilepsy in high‐income countries: A systematic review from the Mortality Task Force of the International League Against Epilepsy - Thurman, David J.; Logroscino, Giancarlo; Beghi, Ettore; Hauser, W. Allen; Hesdorffer, Dale C.; Newton, Charles R.; Scorza, Fulvio Alexandre; Sander, Josemir W.; Tomson, Torbjörn (Epilepsia (Copenhagen), 2017)
Summary Since previous reviews of epidemiologic studies of premature mortality among people with epilepsy were completed several years ago, a large body of new evidence about this subject has been published. We aim to update prior reviews of mortality in epilepsy and to reevaluate and quantify the risks, potential risk factors, and causes of these deaths. We systematically searched the Medline and Embase databases to identify published reports describing mortality risks in cohorts and populations of people with epilepsy. We reviewed relevant reports and applied criteria to identify those studies likely to accurately quantify these risks in representative populations. From these we extracted and summarized the reported data. All population‐based studies reported an increased risk of premature mortality among people with epilepsy compared to general populations. Standard mortality ratios are especially high among people with epilepsy aged <50 years, among those whose epilepsy is categorized as structural/metabolic, those whose seizures do not fully remit under treatment, and those with convulsive seizures. Among deaths directly attributable to epilepsy or seizures, important immediate causes include sudden unexpected death in epilepsy (SUDEP), status epilepticus, unintentional injuries, and suicide. Epilepsy‐associated premature mortality imposes a significant public health burden, and many of the specific causes of death are potentially preventable. These require increased attention from healthcare providers, researchers, and public health professionals.